KEMENANGAN KOTAK KOSONG DALAM PEMILIHAN BUPATI DAN WAKIL BUPATI PATI TAHUN 2017 - Aluisia Prita Parahita; Nur Hidayat Sardini; Priyatno Harsasto (Journal of Politic and Government Studies, 2018)
Pati local elections in 2017 which only included one single candidate leaving an interesting political phenomenon. Of the 101 regions in Indonesia that conduct head local election (PILKADA), there are only 9 regions whose Pilkada consists of single candidates, one of them is Pati. In Pati, "empty box" have triumphed in several polling stations. The victory is based on several things and certainly can not be separated from the influence of a social movement that intensely campaigning and influencing people to choose "empty box". The purpose of this study is to find out about the dynamics of the victory of empty box and the winning factors of empty box in the Pati Election of 2017.The method used in this research is the qualitative technique with the method of collecting observation data either through interviews and/or document studies. The selected informants were the citizen in three villages of Margoyoso sub-district and the volunteers of AKDPP and related parties.The results of this research shows that the victory of empt box in a number of Voting Station consists of several stages. And the victory happened is due to the society's disappointment of petahana, the influence of AKDPP social movement and the problem with the construction of a cement plant permit.The recommendation that can be given is the strengthening of civil society, so that the public can control the governance and licensing of AKDPP to become a legitimate and more organized movement by registering to Kesbangpol.Keywords: Local Election, Empty Box Victory, New Social Movement